2005
DOI: 10.1007/s00381-005-1233-2
|View full text |Cite
|
Sign up to set email alerts
|

Positional skull deformities in children: skull deformation without synostosis

Abstract: Most positional head deformities appear to be related with the children's positioning for sleeping. We have not confirmed macrocephaly as a contributing factor for positional deformities. The distribution of extracerebral CSF and the presence of abnormal collections of fluid in children with positional head deformities do not seem to be related with the findings of pericerebral CSF encountered in children with benign extracerebral collections of fluid. In our view, brain pulsations, transmitted to these accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
2
14
0
3
Order By: Relevance
“…Unlike what we expected and what had been published previously [8,13,15,17,21], multiple-birth pregnancy was almost never associated with MBS in our study population, whereas an occipital flattening was described by Peitsch et al in up to 56% of twins [21] and an incidence of 44% of postural asymmetry was reported by Hamanishi and Tanaka [13]. As to infant-dependent factors, the observation that boys are more frequently affected than girls in terms of torticollis and plagiocephaly has frequently been published [4,5,7,15,16,[19][20][21] and could be explained by a greater average birth length. Unlike what could be expected, birth weights and head circumferences were not significant risk factors for MBS, which has also been observed [21].…”
Section: Discussionsupporting
confidence: 41%
“…Unlike what we expected and what had been published previously [8,13,15,17,21], multiple-birth pregnancy was almost never associated with MBS in our study population, whereas an occipital flattening was described by Peitsch et al in up to 56% of twins [21] and an incidence of 44% of postural asymmetry was reported by Hamanishi and Tanaka [13]. As to infant-dependent factors, the observation that boys are more frequently affected than girls in terms of torticollis and plagiocephaly has frequently been published [4,5,7,15,16,[19][20][21] and could be explained by a greater average birth length. Unlike what could be expected, birth weights and head circumferences were not significant risk factors for MBS, which has also been observed [21].…”
Section: Discussionsupporting
confidence: 41%
“…CT reconstruction also ascertained that the intracranial volume of Cranium 14 was approximately 1,200 cm 3 [23]. In addition, the internal surface of the specimen showed marked endocranial convolutions and signs of enlarged subarachnoid spaces, which have been also documented in cases of positional plagiocephaly and of true craniosynostosis [15,30,38]. Regarding etiology of the synostosis, Gracia et al mention the possibility of intrauterine trauma, fetal head constraint, or torticollis The space between the suture borders suggests that there was probably one more supernumerary ossicle.…”
Section: "Benjamina": the Middle Pleistocene Child With True Lambdoidmentioning
confidence: 82%
“…Posterior plagiocephaly refers to an asymmetric shape of the posterior part of the cranium that can be due either to true parieto-occipital bone fusion or to a deformed occiput by external forces [14,19,22,25,30,31,36,38]. The distinction between these two conditions has proven to be quite difficult and some authors include a "sticky" lambdoid suture within the group of lambdoid synostosis [22,25,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occipital positional plagiocephaly (Fig. 2) is associated with asymmetrical "parallelogram" skull shape, unilateral parieto-occipital flattening, ipsilateral frontal bossing, contralateral frontal flattening and occipital bossing, asymmetry of external nose (nasal root is in a midline position but nasal bones and piriform aperture are deviated on the contralateral side), asymmetry of the orbits (contralateral orbit is situated low then ipsilateral orbit), asymmetry of the ear position (ipsilateral ear is situated anterior and superior) (9,11,13,16,21). Positional plagiocephaly can be classified as mild (without facial asymmetry) or severe (with facial asymmetry) (3).…”
Section: Introductionmentioning
confidence: 99%